2018
DOI: 10.17219/acem/68441
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic T-wave parameters in families with long QT syndrome

Abstract: The electrocardiographic Tpeak-Tend parameter, in addition to the QT interval, is helpful in identifying affected blood relatives of children with LQTS, particularly for the group of LQTS1 and LQTS2 women. Further studies are required to assess the clinical importance of the TpTe interval in families with long QT syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It was also found that the Tp-e/QTc ratio is also higher in high-risk patients, making it a useful risk marker. Furthermore, according to Markiewicz-Łoskot et al's study [ 58 ], Tp-e, combined with QTc, may have potential use in detecting affected relatives of people with congenital LQTS. They found that Tp-e is significantly longer in relatives affected by LQTS than in those unaffected and associated this marker with the possibility of cardiac events.…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that the Tp-e/QTc ratio is also higher in high-risk patients, making it a useful risk marker. Furthermore, according to Markiewicz-Łoskot et al's study [ 58 ], Tp-e, combined with QTc, may have potential use in detecting affected relatives of people with congenital LQTS. They found that Tp-e is significantly longer in relatives affected by LQTS than in those unaffected and associated this marker with the possibility of cardiac events.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of repolarization period parameters, especially the TpTe interval, is useful in identifying patients at high risk of serious cardiac arrhythmias also in other clinical conditions such as short QT syndrome [44], long QT syndrome (LQTS) [45], hypertension [46,47], arrhythmogenic right ventricular cardiomyopathy [48], and in competitive sports [49]. The results of our own research are comparable to the opinions of many authors talking about the desirability of assessment in a 12-lead ECG, not only of the duration of the QT interval, but also the TpTe interval of the recognized new arrhythmogenesis index, which is considered a more sensitive prognostic parameter of ventricular arrhythmia compared to the one traditionally determined by QT interval [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The questions of whether the TpTe interval reflects transmural repolarization heterogeneity or total dispersion of repolarization [ 13 , 14 ] is still a matter of debate. Therefore, in clinical practice, the TpTe interval is considered a more sensitive marker of arrhythmogenesis and increased risk of mortality in long QT syndrome (LQTS) compared to the QT interval [ 7 , 15 ]. In clinical evaluation, the TpTe interval, in addition to the QT interval, has been found amplified in patients with congenital and acquired LQTS [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%